The Colorimetric Isothermal Multiple-Self-Matching-Initiated Amplification Using Cresol Red for Rapid and Sensitive Detection of Porcine Circovirus 3 - Gou, Hongchao; Bian, Zhibiao; Cai, Rujian; Jiang, Zhiyong; Song, Shuai; Li, Yan; Chu, Pinpin; Yang, Dongxia; Zang, Ying-An; Li, Chunling (Frontiers in Veterinary Science, 2020)
In 2016, a novel porcine circovirus (PCV), PCV3, was identified in USA. Subsequently, it was proved to be also epidemic in China, Poland and Korea. To analyse and control the epidemic situation of PCV3, it is necessary to establish accurate and high-throughout detection methods. In this study, the colorimetric isothermal multiple-self-matching-initiated amplification (IMSA) using cresol red was developed to detect PCV3 for the first time. The reaction can be easily performed by incubating the tube at 63°C for 60 min. By the addition of pH-sensitive indicator dye cresol red, the initial color of the reaction mixture is red. When PCV3 capsid gene DNA was positive in the sample, the color of the reaction mixture changed from red to yellow after the isothermal incubation at 63°C, while the negative control maintained red color. Moreover, the colorimetric IMSA displayed good specificity in detecting PCV3, PCV2, PCV1 and 4 porcine DNA pathogens. And it has a low and repeatable detection limit of 10 copies, which is consistent with TaqMan-based qPCR, but 10 times more sensitive than PCR. In diagnosing 128 clinical specimens, it not only showed 100% agreement with qPCR, but also detected 15 positive results more than PCR. The colorimetric IMSA we offered might be a good choice for PCV3 epidemiological investigation and point-of-care testing.